Effects of workplace violence on the quality of care by nurses: A study of the Volta Region of Ghana - Foster Mensah Kofi Agbornu; Isaac Mensah Boafo; Adelaide Maria Ansah Ofei (Elsevier, 2022)
This study examined the incidence of workplace violence (WPV) against nurses and its effect on quality of care. A cross-sectional survey was conducted among 584 nurses working in public hospitals in the Volta Region. Almost twelve percent of the respondents experienced physical violence during the period under study. Although patients' relatives were the most frequent perpetrators, it is disturbing to note that almost a fifth (17.1%) of all physical violence cases recorded in this study were perpetrated by supervisors and other staff members. There was a significant association between physical violence and the rank of the nurse (X2 = 14.196, df = 4, N = 584, p =.01). In relation to quality of care, we found that WPV was statistically significantly associated with a decline in all the facets of quality of care. It, for instance, impacted negatively on nurses' relationship with patients (X2 = 26.862, df = 1, N = 41, p =.000). We suggest enhanced public awareness campaign and increased support for victims of workplace violence.